Manaaki Tāngata: The Application of Kaupapa Māori as an Ideological Base for a Caregiving Programme for Māori Youth and Whānau at Risk - Kaipo, Martin (Auckland University of Technology, 2018)
Since British colonisation and the signing of the Treaty of Waitangi in 1840, Māori have consistently endured social disparities which have disadvantaged whānau (family, extended family) hapū (sub-tribe) and iwi (tribe) and their aspirations to achieve wellness. This exegesis will critically examine the history of care-practice of Māori youth and whānau in Aotearoa New Zealand including an analysis of the policy which governs care-provision and practice in Aotearoa New Zealand demonstrating that Māori remain underprivileged. This analysis will highlight the State’s failure to incorporate Kaupapa Māori (Māori ideology) into mainstream policy despite the recommendations in the 1988 Puao-te-ata-tu – The Report of the Ministerial Advisory Committee on a Maori [sic] perspective for the Department of Social Welfare, headed by the late John Te Rangianiwaniwa Rangihau. Furthermore, this exegesis will present a case-study of a successful Māori community service provider that operates from a Kaupapa Māori philosophical base and is therefore consistent not only with whānau, hapū, iwi aspirations of family wellness, but consistent with the recommendations in Puao-te-ata-tu. Without the amalgamation of Kaupapa Māori ideology and values into Māori care provision in Aotearoa New Zealand, Māori will continue to experience serious disparities and unwellness. A visual report of 32 minutes is the creative component of this research project and complements the text, particularly the case-study of Otangarei Trust and thereafter, the Te Hau Āwhiowhio o Otangarei Trust.
Keywords: Manaaki Tāngata; Care-giving; Māori youth; Whānau; Te Hau Āwhiowhio o Otangarei Trust